Clay Matters : Thinking and Exhibiting Matter in Recent Art. - Geerts, Martine (Hasselt : PXL-MAD, 2017)
Coolen, Caroline ; Creten, Johan ; Engelfriet, Alexandra ; Fink, Christoph ; Manders, Mark ; Meuris, Wesley ; Naveau, Nadia ; Pacquée, Ria ; Pauwels, Marieke ; Reijnders, Anton ; Schütte, Thomas ; Schwindt, Grace ; Wenzel, Anne
kunstcatalogus